Distribution of CSL grain boundaries in oriented cemented carbides. Issue 3 (18th December 2015) - Wang, Xilong; Song, Xiaoyan; Wang, Haibin; Liu, Xuemei; Liu, Xingwei; Guo, Guangsheng
Abstract : The anisotropy of distributions of specific WC planes and coincidence site lattice (CSL) grain boundaries can be tailored by adjusting the composition of the WC–Co composite powder and its sintering parameters. Abstract : WC–Co cemented carbide bulk materials with anisotropic distribution of specific WC planes were prepared by spark plasma sintering (SPS) using different pre-sintering temperatures of 850 °C, 900 °C and 1000 °C at a constant pressure of 60 MPa. The coincidence site lattice (CSL) grain boundaries were characterized and the anisotropic distribution of the CSL boundaries was demonstrated. The combined effects of the composite powder and the SPS parameters on the formation of the anisotropic CSL boundary distribution were analyzed. The mechanisms were proposed such that the CSL grain boundary distribution can be tailored by adjusting the composition of the composite powder and the SPS processing parameters such as the pre-sintering temperature, sintering pressure and its working stage. The findings facilitate to obtain a beneficial CSL grain boundary distribution that enhances mechanical properties in certain directions of the cemented carbide.